2022
DOI: 10.3390/cancers14133085
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Ethnic Inequalities in Diagnostic Interval of Common Cancers: A Population-Based UK Cohort Study

Abstract: Background: This study investigated ethnic differences in diagnostic interval (DI)—the period between initial primary care presentation and diagnosis. Methods: We analysed the primary care-linked data of patients who reported features of seven cancers (breast, lung, prostate, colorectal, oesophagogastric, myeloma, and ovarian) one year before diagnosis. Accelerated failure time (AFT) models investigated the association between DI and ethnicity, adjusting for age, sex, deprivation, and morbidity. Results: Of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Moreover, the time Black patients spend waiting to receive cancer diagnosis is significantly longer than that of White patients both in the United States ( 42 ) and the United Kingdom. ( 43 ). Our study contributes to this line of this research by showing that Black scientists in the United States suffer from longer delays before their manuscript is accepted for publication.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the time Black patients spend waiting to receive cancer diagnosis is significantly longer than that of White patients both in the United States ( 42 ) and the United Kingdom. ( 43 ). Our study contributes to this line of this research by showing that Black scientists in the United States suffer from longer delays before their manuscript is accepted for publication.…”
Section: Discussionmentioning
confidence: 99%
“… 41–50 This finding is reinforced within recent findings that black and Asian patients wait up to a month longer than white patients for some cancer diagnoses. 71 Rural residence and being part of a VSG also appear linked to limited treatment access 51–56 including access to timely and appropriate care. 58 59 72 Multiple studies demonstrated the negative impact of deprivation on access to surgery, 48 60 61 73 a finding consistent with previous work which found that low socioeconomic position reduced the likelihood of receipt of any type of LC treatment, surgery or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a small proportion of women had breast pain, which was recorded as an isolated feature in over half of Black women with that feature. These women may form the bulk of those experiencing greater pre-referral consultations and longer times to diagnosis [ 10 , 11 ], since isolated breast pain is less predictive of cancer [ 31 , 34 , 35 ], with no current UK recommendation for urgent investigation. Breast pain has been linked to a greater risk of advanced-stage breast cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent multi-method study of UK men presenting with possible prostate cancer symptoms in primary care showed that men, particularly Black men, may not fully disclose their concerns or symptoms during initial consultations, partly due to the relatively short duration of primary-care consultations [ 9 ]. Non-disclosure of symptoms may explain the greater frequency of primary-care consultations [ 10 ] and the longer time to diagnosis among the UK Asian and Black groups compared with the White group [ 11 ], although this aspect has not been fully examined. In the present study, we used cancer-registry-linked data to investigate possible ethnic differences in the number and type of cancer features recorded in primary care before a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%